External quality assessment for warfarin dosing using computerised decision support software - Oppenkowski, T P (Copyright 2003 Journal of Clinical Pathology, 2003)
Aim: To establish and evaluate an external quality assessment scheme for warfarin dosing for users of a computerised decision support system, BAP-PC. Design: Analysis of 12 months of clinical data from 10 primary care centres using BAP-PC within an oral anticoagulation clinic. Data were analysed for individual centres and compared with aggregated data for all practices. Individual feedback forms were provided to participating centres. Results: A total patient population of 367 (range, 17–65/centre) was analysed. On average, patients spent 69% of time in the therapeutic range (range, 60–76%). Patients were seen on average every 27 days (range, 24–30). The average point prevalence was 86% (range, 76–100%). In total, 33 adverse events were reported (0–13/practice). Serious adverse events ranged from 0 to 1 for each practice. This translates into a serious adverse event rate of 1.6/100 patient years. Conclusions: Practices were successful in maintaining good therapeutic international normalised ratio control, with centres achieving 60% or higher time in range. There are some doubts about the quality of data collection at a practice level because there were no reported events in half of the participating centres. The observed event rates do concur with previously reported data, however. Further cycles of the scheme are necessary to establish it as a useful research and benchmarking tool.